Using Google Scholar to Determine the Most Cited Criminology and Criminal Justice-Related Books - Gabbidon, Shaun L. (American journal of criminal justice, 2012)
Building on recent research investigating the role of books in the discipline of criminology and criminal justice (C/CJ), this paper uses Google Scholar to identify the most cited books in the field. In particular, the researchers examined the most cited books in four different eras. Prior to1900, the most cited C/CJ-related book was On the Origin of Species . Merton’s Social Theory and Social Structure was the most cited book in the second era (1900–1949). The third era (1950–1999) produced the most cited work in the study, Foucault’s Discipline & Punish . And in the final era (2000 to present), Garland’s Culture of Control was the most cited work. The researchers also sought to determine the most cited books by women and African Americans/Blacks. The most cited book by a female author was Judith Herman’s Trauma and Recovery , and the most cited book by an African American/Black scholar was William Julius Wilson’s The Truly Disadvantaged . The authors conclude by arguing for the continued emphasis on demarcating the “great books” in the discipline.